Desgaste e vida de ferramenta no torneamento de uma liga à base de níquel - Marcasso, Wanderson (Universidade Federal de São Carlos, 2023)
In the field of metal alloy machining, materials predominantly composed of nickel alloys, with a focus on Inconel 718, present notable challenges, stemming from the interplay of intense cutting forces and extreme temperatures in the cutting zone. This combination triggers accelerated wear on cutting tools. This study proposes a meticulous investigation of standardized turning parameters, using robust and widely recognized criteria to discern their relevance and optimization potential. We centered our analysis on multifaceted wear modes, encompassing flank wear, crater wear, and the emerging formation of built-up edge, during the machining process, using meticulously selected commercial inserts for this purpose. The application of the Taylor model was chosen, an approach revered both in the academic world and in the industrial sector, aiming for a discerning evaluation of the wear of cutting tools and interpreting their intrinsic behavior in machining nickel alloys. The research conclusions revealed eminent findings regarding the correlation between cutting parameters and tool wear, laying solid groundwork for future strategies aimed at extending tool durability and refining the quality of the final machined product.
Tool wear and tool life in turning a nickel-based alloy
Keywords: Usinagem; Torneamento; Super Ligas de Níquel; Inconel; Modelo de Taylor; Desgaste; ENGENHARIAS::ENGENHARIA MECANICA::PROCESSOS DE FABRICACAO